A block-based variational elasto-damage model for masonry analysis inspired from granular micromechanics: Preliminary study. (December 2021) - Tran, C.A.; Barchiesi, E.; Placidi, L.; León Trujillo, F.J.
Abstract: We develop a new block-based elasto-damage model for describing masonry structures. The constitutive elastic and damage behavioural laws used within the proposed approach are inspired from those employed in the recent literature in granular micromechanics. Adaptations have been made in many respects, notably the inclusion of impenetrability constraints through energy barriers. The analysis carried out in this paper proves that realistic masonry deformation modes can be obtained. Highlights: A new block-based model for the static failure mode analysis of masonry panels. Masonry modelled as rigid blocks with damageable elastic links. Variational approach: minimisation of energies inspired from granular micromechanics. Preliminary simulations show realistic static failure modes. Future extension to dynamic damageable elasto-plastic analysis of masonry structures.